Thematic and genre and style features of early prose by Arthur Schnitzler (Literatures of the World: Poetics, Mentality and Spirituality, 2015)
The article deals with the origins of the poetics of aesthetic and ideological sources of creativity Arthur Schnitzler (1862 – 1931). Revealed the basic artistic principles that define the genre and stylistic features of works of art lingvostilistik techniques, thematic meaning of the dominant prose of the Austrian writer.
Keywords: an early prose; a short story; a style; a motive; conceptualization; a hero; image-creation